Steam reforming of acetic acid over Ni/ZrO2 catalysts: Effects of nickel loading and particle size on product distribution and coke formation - Li, Z.; Hu, Xun; Zhang, Lijun.; Liu, Shaomin; Lu, G. (Elsevier B.V., 2012)
Steam reforming of acetic acid has been carried out over a series of Ni/ZrO2 catalysts to measure the effects of nickel loading on distribution of the reforming products and coke formation. Ni (≤13 wt.%)/ZrO2 catalysts do not contain enough active metal sites for steam reforming of both acetic acid and organic by-products. Ni (≥20 wt.%)/ZrO2 catalysts can effectively catalyze steam reforming but lack selectivity, since methanation and reverse water gas shift reactions are promoted, leading to low hydrogen yields. Ni (16 wt.%)/ZrO2 catalyst is the most selective one, due to its low activity to the secondary reactions that contribute to by-product production. Coke formation is suppressed with the increase of nickel loading up to 16 wt.%, and then restarts to increases with the further increase of nickel loading. Polymerization of acetone is the main route for coke deposition over the Ni (≤13 wt.%)/ZrO2 catalysts. Methane decomposition and CO disproportion are the two main routes for coke formation over the Ni (≥20 wt.%)/ZrO2 catalysts, and methane contributes more to coke formation than CO. In addition, activity of Ni/ZrO2 catalyst towards the secondary reactions such as methanation, reverse water gas shift reaction, methane decomposition, and CO disproportion are closely related to nickel loading and nickel particle sizes.